2005
DOI: 10.1074/jbc.m508175200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Nonstructural Protein 5A (NS5A) Is an RNA-binding Protein

Abstract: Hepatitis C virus (HCV) nonstructural protein 5A (NS5A) has been shown to antagonize numerous cellular pathways, including the antiviral interferon-␣ response. However, the capacity of this protein to interact with the viral polymerase suggests a more direct role for NS5A in genome replication. In this study, we employed two bacterially expressed, soluble derivatives of NS5A to probe for novel functions of this protein. We find that NS5A has the capacity to bind to the 3-ends of HCV plus and minus strand RNAs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
234
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 229 publications
(248 citation statements)
references
References 56 publications
9
234
2
3
Order By: Relevance
“…HCV NS5A is a phosphoprotein with no known enzymatic activity that plays an essential, although poorly understood, role in the viral life cycle. NS5A is required for RNA replication, for infectious HCV assembly, and for interactions with a variety of cellular proteins (22)(23)(24); the NS5A protein is also the target of the most potent anti-HCV inhibitors discovered to date (25). The largest TDAV NS5A insertion resides in the equivalent of HCV NS5A domain I, a zinc-binding region with RNA-binding activity (26,27); the relevance of the insertions in the TDAV life cycle is not known.…”
Section: Discussionmentioning
confidence: 99%
“…HCV NS5A is a phosphoprotein with no known enzymatic activity that plays an essential, although poorly understood, role in the viral life cycle. NS5A is required for RNA replication, for infectious HCV assembly, and for interactions with a variety of cellular proteins (22)(23)(24); the NS5A protein is also the target of the most potent anti-HCV inhibitors discovered to date (25). The largest TDAV NS5A insertion resides in the equivalent of HCV NS5A domain I, a zinc-binding region with RNA-binding activity (26,27); the relevance of the insertions in the TDAV life cycle is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic part of NS5A is composed of a well structured domain 1 (D1) and two intrinsically disordered domains (D2 and D3) that exist as highly dynamic interconverting conformers. NS5A-D1, which is the target of daclatasvir (7,17), contains a zinc finger motif and possesses RNA binding properties (18). Crystallographic studies revealed that this domain could adopt at least three different homodimeric conformations (19 -21), underscoring the multifunctionality of the protein.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…The basic groove in the inner side of the claw is positioned away from the membrane and could interact with RNA (38). It was found that bacterially expressed NS5A binds to the 3Ј-end of HCV positive and negative strand RNA with a preference for the poly(U/UC) tract in the 3Ј-NTR of positive strand RNA (39). Conceivably, NS5A dimers might oligomerize into large two-dimensional assemblies forming an extended groove.…”
Section: Components Of the Hcv Replication Complexmentioning
confidence: 99%